The Role of Root Canal Preparation on Apical Geometry: A Review of the Literature - Zahed Mohammadi; Jun-Ichiro Kinoshita; Atsufumi Manabe; Mikihiro Kobayashi; Sousan Shalavi; Flavio Palazzi; Hamid Jafarzadeh (Mashhad University of Medical Sciences, 2019)
The amounts of apical enlargement have been a controversial issue for a long time. The enlargement of the apical part of the canal may severely impact the endodontic prognosis. Enlargement of the apical portion to a larger size may negatively affect the ability to control the filling material during root canal obturation. In addition, an open-apex increases the risk for overfilling which has been shown to be related with decreased success rate. The retreatment of a tooth with apically enlarged canal may be even impossible. Further preparation of an apically enlarged canal may increase the risk of iatrogenic errors and also excessive apical root weakness. The present article aimed to address in vitro and clinical studies on apical enlargement, effect of coronal pre-flaring on the size of the master apical file, and clinical applications of apical enlargement.